2021
DOI: 10.5194/tc-2021-216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A strong link between variations in sea-ice extent and global atmospheric pressure?

Abstract: Abstract. Abstract. This paper reports spectral analyses, using Singular Spectral Analysis, of variations of the Arctic and Antarctic sea-ice extents (SI), and of the atmospheric surface pressure (AP) in both hemispheres (NH and SH). The ice-extents are dominated by a quasi-linear trend over the 42 yr period when data are available (1978–2020) and an annual component. Taken together, these two components represent more than 98 % of the signal variance. Both ice-extent series share the same 5 set of harmonics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Laplace assumes that all masses on and in Earth are set into motion by astronomical forces. As already shown in a previous work (see Le Mouël et al, (2021b), figure 03), the trends observed in the time series are quasi linear, decreasing for NHSI (by 58.300 km 2 /yr) and increasing for SHSI (by 15.400 km 2 /yr). The amplitude of annual variations in the Antarctic is double that in the Arctic, they are in phase opposition and modulated, with a flat trend for SHSI, a decreasing trend for NHSI and a sub-decadal modulation of the envelopes.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Laplace assumes that all masses on and in Earth are set into motion by astronomical forces. As already shown in a previous work (see Le Mouël et al, (2021b), figure 03), the trends observed in the time series are quasi linear, decreasing for NHSI (by 58.300 km 2 /yr) and increasing for SHSI (by 15.400 km 2 /yr). The amplitude of annual variations in the Antarctic is double that in the Arctic, they are in phase opposition and modulated, with a flat trend for SHSI, a decreasing trend for NHSI and a sub-decadal modulation of the envelopes.…”
supporting
confidence: 85%
“…This is already known regarding the variations of the sea-ice dipole in Antarctica (cf. Holland et al (2017); Bertler et al (2018); Le Mouël et al (2021b) and the variations of the trends of global atmospheric pressure (cf. (Lopes et al 2022b)).…”
Section: Discussionmentioning
confidence: 99%
“…This is already known regarding the variations of the sea ice dipole in Antarctica (cf. [69][70][71]) and variations in the trends of global atmospheric pressure (cf. [6]).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to short-term timescales and tidal periodicities, these multi-annual to centennial variations are present in other geophysical parameters. Most of them record both tidal and solar periodicities, as illustrated by the magnetic field (e.g., Bartels, 1932;Le Mouël, 1984;Courtillot and Le Mouël, 1988;Jault, 1990;Le Mouël et al, 2019), polar motion (Lopes et al, 2017;Lopes et al, 2021a;Lopes et al, 2022a), sea level observed from local and global data (e.g., Chambers et al, 2012;Wahl and Chambers, 2015;Le Mouël et al, 2021a;Courtillot et al, 2022a), global surface air temperatures (e.g., Courtillot et al, 2013;Le Mouël et al, 2020b;Scafetta, 2021), and more generally, climate (e.g., Wood and Lovett, 1974;Schlesinger and Ramankutty, 1994;Scafetta, 2010;Courtillot et al, 2013;Scafetta, 2016;Le Mouël et al, 2019c;Le Mouël et al, 2021b). Moreover, these links also seem to exist 1) on much longer timescales of millennia, governed by astronomical configurations and impacting climate and sedimentation (e.g., Milanković, 1920;Kutterolf et al, 2013;Coussens et al, 2016;Kutterolf et al, 2019;Lopes et al, 2021b;Satow et al, 2021); and 2) also for earthquakes, as suggested by numerous studies (e.g., Tamrazyan, 1968;Mazzarella and Palumbo, 1988;Marchitelli et al, 2020).…”
Section: Periodicities Detected In Volcanic Activity and Other Geophy...mentioning
confidence: 99%